A new genus and species of xenodermatid snake (Squamata: Caenophidia: Xenodermatidae) from northern Lao People’s Democratic Republic - Teynié, Alexandre; David, Patrick; Lottier, Anne; Le, Minh Duc; Vidal, Nicolas; Nguyen, Truong Quang (Zootaxa, 2015)
A male snake collected in Louangphabang Province and a second specimen observed in Houaphan Province, North Laos, share morphological characters with the Asian genus Fimbrios Smith, 1921, including erected edges on the first supra- and infralabial scales, but differ in the following morphological characters: fewer dorsal scale rows (25–27 vs. 30–33), fewer maxillary teeth (27 vs. 30–35), posterior teeth progressively slightly enlarged, and especially the correspondence of two dorsal scale rows per ventral plate throughout the body (i.e. the first dorsal scale row made of a small scale above the fore part of a ventral, followed by a much larger scale above its hind part), a condition known only in Xenodermus Reinhardt, 1836. As the Laotian specimens differ in morphological characters from other genera and species in the family Xenodermatidae, and on the basis of molecular analyses showing a large genetic divergence from the genus Fimbrios (p-distance ≥14.7 %, mitochondrial COI gene), we place these specimens in a new genus, Parafimbrios gen. nov., and describe them as a new species, Parafimbrios lao sp. nov. Besides the characters mentioned above, the new species is diagnosed by a combination of the following ones: small, strongly keeled dorsal scales; rostral and first four supra- and infralabials with raised, erected edges; horizontal tissue ridges above the rostral; loreal single, large, elongate; ventral scales 177–189; subcaudals 55–56, undivided; dorsal colour purplish-grey, neck with a broad, very pale grey collar reaching downwards the pale grey colour of the venter. The morphological characters of the new genus are compared with those of the genera Fimbrios Smith, 1921, Xenodermus Reinhardt, 1836, Stoliczkaia Jerdon, 1870, Achalinus Peters, 1869, and Xylophis Beddome, 1878. A key to the genera Achalinus, Fimbrios and Parafimbrios gen. nov. is provided. Parafimbrios laos spec. nov. is the 111th snake species currently recorded from Laos.